Crack nucleation and propagation in microcrystalline-cellulose based granules subject to uniaxial and triaxial load - Jonsson, Henrik; Öhman-Mägi, Caroline; Alderborn, Göran; Isaksson, Per; Frenning, Göran (International journal of pharmaceutics, 2019)
[Display omitted] Cracking patterns in four kinds of granules, based on the common pharmaceutical excipient microcrystalline cellulose (MCC) and subject to compressive load, were examined. The initial pore structure and the location of initial failure under uniaxial compression were assessed using X-ray micro-computed tomography, whereas contact force development and onset of cracking under more complex compressive load were examined using a triaxial testing apparatus. Smoothed particle hydrodynamics (SPH) simulations were employed for numerical analysis of the stress distributions prior to cracking. For granules subject to uniaxial compression, initial cracking always occurred along the meridian and the precise location of the crack depended on the pore structure. Likewise, for granules subject to triaxial compression, the fracture plane of the primary crack was generally parallel to the dominant loading direction. The occurrence of cracking was highly dependent on the triaxiality ratio, i.e. the ratio between the punch displacements in the secondary and dominant loading directions. Compressive stresses in the lateral directions, induced by triaxial compression, prevented crack opening and fragmentation of the granule, something that could be verified by simulations. These results provide corroboration as well as further insights into previously observed differences between confined and unconfined compression of granular media.